2010
DOI: 10.1590/s1414-81452010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Relação de ajuda no desempenho dos cuidados de enfermagem a doentes em fim de vida

Abstract: Este estudo tem como principal objetivo verificar a importância que os enfermeiros atribuem às competências relacionais na ajuda a doentes em fim de vida. A investigação é de tipo descritivo-correlacional, transversal, com uma amostra de 56 enfermeiros, selecionada de forma intencional, acidental e desenvolvida a partir da aplicação de um instrumento de medida que integra o Inventário de Competências Relacionais de Ajuda, Escala de Satisfação com a Vida, Questões relativas à importância atribuída à formação co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 1 publication
3
12
1
2
Order By: Relevance
“…In terms of the correlation between student gender and total ICRA score, we found that the mean score for total helping relational skills among men was slightly higher than among women (although the difference was not statistically significant). This finding corroborates that of another study conducted with nurses in which "men seemed to present, even if slightly, higher values of overall helping relational skills compared with women" (10) . Nonetheless, regarding the overall scale score, the results of that study showed that:…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In terms of the correlation between student gender and total ICRA score, we found that the mean score for total helping relational skills among men was slightly higher than among women (although the difference was not statistically significant). This finding corroborates that of another study conducted with nurses in which "men seemed to present, even if slightly, higher values of overall helping relational skills compared with women" (10) . Nonetheless, regarding the overall scale score, the results of that study showed that:…”
Section: Discussionsupporting
confidence: 90%
“…Female students presented higher means in all dimensions of helping relational skills and developed their generic, empathetic and communication skills significantly better than men. Regarding contact skills, no statistically significant differences were found between genders (10) .…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations